Pengaruh Stres Kerja, Motivasi Kerja Dan Kompensasi Terhadap Kinerja Karyawan BPJS Ketenagakerjaan Jajaran Kanwil Sulawesi - Maluku - Irham Hasyim; Jeni Kamase; Serlin Serang (Departement of Mathematics Education, 2023)
This research was conducted with the aim of; (1) examine and analyze the effect of work stress on performance; (2) examining ananalyzingze the effect of motivation on performance; and (3) analyzing the effect of compensation on the performance of BPJS Ketenagakerjaan employees at the Regional Offices of Sulawesi - Maluku. This study uses primary data using the sampling method, namely the Simple Random Sampling method through a survey of 81 employees as a sample with a minimum working period of 1 year as of February 2023, the survey was conducted from January 2023 to February 2023. Data were analyzed using the SPSS 24 program. The results of this study indicate that: (1) Job stress has a positive and significant effect on performance; (2) Motivation has a positive and significant influence on performance; and (3) Compensation has a positive and significant influence on the Performance of Employees of BPJS Ketenagakerjaan in the Regional Offices of Sulawesi - Maluku. This means the dimensions of workload, authority, physical condition, discomfort, and work pressure. Furthermore, the necessities of life, superior praise, incentive,s and attention. Then the dimensions of salary, benefits, incentives, and facilities. Likewise dimensions of quality, quantity, timeliness, effectiveness, facilities, and infrastructure. These dimensions can encourage the achievement of increased employee performance which is useful for the development of work productivity at the Employment BPJS for the Sulawesi Regional Offices - Maluku.